Experimental studies on the flow characteristics of a centralized exhaust system with multiple distribution of open terminals. (October 2021) - Zeng, Lingjie; Wang, Yirui; Gao, Jun; Du, Bowen; Tong, Leqi; Liu, Guodong; Cao, Changsheng; Zhang, Chengquan; Xu, Yukun
Abstract: In the scenarios of cooking oil fume exhaust in high-rise residential buildings and pollutants removal in industrial workshops, how to realize the exhaust uniformity is a problem. We discovered through our previous work that installing flow-guide devices at terminals within the exhaust system can greatly improve the exhaust uniformity of the system, but in-depth experimental studies on the flow balance characteristics of such devices under different influential factors are required. Therefore, this study aims to verify the effect of the proposed flow-guide devices on improving the exhaust performance of the system through a full-scale experiment considering multiple factors. First, the key parameter of the flow-guide device was identified. Then, the exhaust air volume and pressure of the terminals were tested under various opening modes and coincidence factors. Finally, error, significance and variance analyses were performed to process the experimental data comprehensively. Results show that the system with flow-guide devices exhibited a considerably improved exhaust uniformity compared with the system without such devices. Meanwhile, the use of flow-guide devices alters the function of the coincidence factors and the opening modes of the terminals in the exhaust uniformity and energy consumption of the system. Furthermore, the proposed devices are suitable for scenarios with a high coincidence factor. The novelty of this work is to comprehensively test the effect of flow-guide devices on the exhaust uniformity and energy consumption of the centralized exhaust system, accumulating experimental data for future engineering applications. Highlights: The exhaust uniformity of the centralized exhaust system is improved by installing flow-guide devices. By installing devices, the impact of the coincidence factor on the exhaust uniformity becomes insignificant. The application of such devices has energy saving potential if the coincidence factor is large and stable.